Anatomico-Clinical Insights from a Rare Unilateral Bifurcation Of The Fibularis Brevis Tendon: A Dissection Report With A Proposal to Improve The Classification System - Gaydarski L.; Landzhov B.; Mirazchiyski G.; Angushev I.; Piagkou M.; Georgiev G. P. (Acta Medica Bulgarica)
The lateral compartment of the foot encompasses two muscles: the fibularis brevis and fibularis longus (FB and FL). The FB originates from the distal two-thirds of the fibula in conjunction with the adjacent intramuscular septa. Variations concerning the origin, number of muscle bellies, and insertions of the FB have been frequently documented. However, bifurcation of the fibularis brevis tendon (FBT) represents a rare variant seldom described in the literature. The present dissection report details a rare occurrence of a FBT bifurcation. Following the passage beneath the inferior Tibular retinaculum, the tendon bifurcates into a superior and an inferior slip. The superior slip is inserted into the fifth metatarsal base, while the inferior slip extends anteriorly and attaches to the extensor aponeurosis of the fifth toe. Such variations in the course and insertion of the FBT are of clinical significance, given the frequent involvement of this tendon in ankle injuries and its critical role in reconstructive surgery. Consequently, medical professionals need a comprehensive understanding of potential variants in the origin, trajectory, and insertion ofthe FB and its tendon.